2016
DOI: 10.1001/jamaophthalmol.2016.1784
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With the Ophthalmoscopic Findings Identified in Infants With Presumed Zika Virus Congenital Infection

Abstract: IMPORTANCE The Zika virus (ZIKV) might cause microcephaly and ophthalmoscopic findings in infants of mothers infected during pregnancy. OBJECTIVE To assess and identify possible risk factors for ophthalmoscopic findings in infants born with microcephaly and a presumed clinical diagnosis of ZIKV intrauterine infection. DESIGN, SETTING, AND PARTICIPANTS We conducted a cross-sectional study at the Altino Ventura Foundation in Recife, Brazil, that included 40 infants with microcephaly born in Pernambuco state, Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
2
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(158 citation statements)
references
References 20 publications
9
140
2
4
Order By: Relevance
“…Consequently, there has been significant interest in understanding the pathogenesis of ZIKV in nonneurological diseases. Because clinical studies have linked ZIKV to ocular abnormalities, primarily in the retina of infants (8,12) and adults (45,46) and uveitis in adults (45), it is important to study ZIKV pathogenesis in the eye to identify potential targets for intervention. We have shown that direct inoculation of ZIKV in the adult mouse eye results in retinal lesions with a clinical presentation (chorioretinal atrophy and RPE mottling) resembling some of the features of ZIKV-associated ocular pathology described in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there has been significant interest in understanding the pathogenesis of ZIKV in nonneurological diseases. Because clinical studies have linked ZIKV to ocular abnormalities, primarily in the retina of infants (8,12) and adults (45,46) and uveitis in adults (45), it is important to study ZIKV pathogenesis in the eye to identify potential targets for intervention. We have shown that direct inoculation of ZIKV in the adult mouse eye results in retinal lesions with a clinical presentation (chorioretinal atrophy and RPE mottling) resembling some of the features of ZIKV-associated ocular pathology described in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In view of limited data, microcephaly may represent only one possible adverse outcome among a spectrum of conditions of congenital Zika syndrome (4). Indeed, several clinical studies have reported ocular abnormalities, specifically in the retina and choroid, of infants with congenital ZIKV infection (8)(9)(10)(11)(12)(13). Although currently undetermined, if a causal link between ZIKV infection and ocular disorders is established conclusively, it will have significant long-term economic, psychological, and health implications.…”
Section: Introductionmentioning
confidence: 99%
“…In another Brazilian case series, which included 29 infants with microcephaly and presumed CZS, more than one-third of the children had ocular abnormalities. 21 In a report of 40 infants with microcephaly and presumed CZS from Pernambuco, Brazil, Ventura et al 22 described ophthalmoscopic alterations in 55% (n ¼ 22) of the infants.…”
Section: Ocular Abnormalitiesmentioning
confidence: 99%
“…[21][22][23][24][25] Musculoskeletal, Genitourinary, and Pulmonary Abnormalities Musculoskeletal abnormalities are frequently described in published reports of CZS, but their actual prevalence among infants of women infected during pregnancy remains unknown. Schwartz 9 analyzed 9 reported autopsies of fetuses and infants with intrauterine ZIKV infection and congenital microcephaly; of which 6 had variable findings of craniofacial malformations, craniosynostosis, and limb abnormalities, which included contractures of multiple joints or arthrogryposis.…”
Section: Ocular Abnormalitiesmentioning
confidence: 99%
“…Bu nedenle araştırmacılar Zika virus ile enfekte hastaların yalnızca %10-15'inde konjunktivit geliştiğini ve bu nedenle konjunktivitin ayırıcı tanıda önemi olmadığı sonucuna varmışlardır (31) . Konjenital Zika virus enfeksiyonlarında bildirilen oküler anormallikler; fokal pigment birikimleri, koryoretinal atrofi, optik sinir anormallikleri, iris kolobomu, lens subluksasyonu, maküler pigment birikimi, foveal refleks kaybı, makula atrofisi, bilateral hipersensitif iridosiklit, üveit ve mikroftalmidir (9,28,29,32,44,45) .…”
Section: Klinikunclassified